A Glucuronic Acid Binding Leguminous Lectin with Mitogenic Activity Toward Mouse Splenocytes - Sang Chan, Yau; Ho Wong, Jack; Bun Ng, Tzi (Protein and Peptide Letters, 2011)
A dimeric 64-kDa lectin was purified from seeds of French bean (Phaseolus vulgaris) cultivar number 1. The purification protocol entailed Q-Sepharose, Affi-gel blue gel, Mono S and Superdex 75. The lectin-enriched fraction was adsorbed on Q-Sepharose and Affi-gel blue gel and desorbed using 1M NaCl in the starting buffer. Hemagglutinating activity was adsorbed on Mono S and eluted with a linear 0.3 - 1 M NaCl gradient. Gel filtration on Superdex 75 yielded a single absorbance peak which appeared as a single 32-kDa in sodium dodecyl sulfate poylacylamide gel electrophoresis. Full hemagglutinating activity was observed when the lectin was exposed to a pH ranging from 3 to 11. About 50% activity remained at pH 12, and about 25% at pH 0 to pH 2. Activity was totally abolished at pH 13 - 14. The activity was completely preserved when the ambient temperature was 20°C - 60°C. However, only 50% and 12.5% of the activity remained at 65°C and 70°C, respectively. Activity was barely discernible at 75°C and completely abrogated at and above 80°C. Hemagglutinating activity of the lectin was inhibited by glucuronic acid. Maximum mitogenic activity of the lectin toward murine splenocytes occurred at a lectin concentration of 0.488 μM. The mitogenic activity was nearly eliminated in the presence of 250 mM glucuronic acid. The lectin did not exhibit antiproliferative activity toward hepatoma (HepG2) cells, breast cancer (MCF7) cells, and nasopharynegeal carcinoma CNE stage 1 and stage 2 cells. It was also devoid of significant anti-HIV reverse transcriptase activity.
Keywords: polysaccharides